Ribo-seq and RNA-seq analyses enrich the regulatory network of tomato fruit cracking - Zhaojiang Zhong; Zhen Wu; Rong Zhou; Xiaowei Yu; Yuanyuan Zhou; Yinghao Zhai; Haowei Lin; Fangling Jiang (BMC Plant Biology)
Abstract Tomato (Solanum lycopersicum L.), one of the most widely grown vegetable crops in the world, faces cracking problems before and after harvest. Fruit cracking reduces the commercial value and seriously affects the economic performance of the fruits by affecting the appearance and quality of the fruit. Clarifying the molecular mechanism underlying tomato fruit cracking is of great importance for selecting and breeding cracking-resistant varieties. At present, research on the molecular mechanism of tomato fruit cracking has made progress, but few studies have been conducted to explore the genes related to fruit cracking regulation using combined multi-omics analysis. We applied Ribo-seq (ribosome analysis sequencing) and RNA-seq (RNA-sequencing) techniques to uncover potential fruit cracking regulatory genes and improve the regulatory network of fruit cracking using extremely cracking-resistant (CR) and cracking-susceptible (CS) tomato genotypes. Combining these two sets of histological data and translation efficiency, 41 genes were identified to be associated with fruit cracking. The genes played functions on hormone synthesis (e.g. Solyc09g089580.4, Solyc07g049530.3), reactive oxygen species regulation (e.g. Solyc08g080940.3), cell wall metabolism (e.g. Solyc04g071070.2, Solyc03g123630.4), aquaporins activity (e.g. Solyc03g096290.3, Solyc10g083880.2), cuticle and wax composition, as well as mineral elements transport (e.g. Solyc10g006660.3, Solyc01g057770.3), while 10 of them were transcription factors (TF) (e.g. Solyc05g015850.4, Solyc08g078190.2). Based on the investigation of the interaction relationship between these genes, the synergistic regulation of multi-gene tomato fruit cracking was predicted. This study suggests that the synergistic action of transcription and translation is an important molecular mechanism in regulating tomato fruit cracking.